Importance of animal feed in the agro-industrial sector - Quintero Serna, César Augusto; Quintero Serna, César Augusto; Quintero Serna, César Augusto (Corporación universitaria Americana, 2022)
The production process of animal feed is part of a chain of activities ranging from the production and importation of raw materials to the results of animal exploitation. In Colombia, the manufacture of animal feed has grown to levels that exceed the average production of the manufacturing industry and make the agro-industrialsector one of the most influential in the country's economy. With the growth of the agroindustry, it is expected to meet the human food requirements in the national territory, which are insufficient to achieve a well-nourished population. With a global focus on cleanerproduction, environmental control policies, and the use of biomass as an alternative food source to the conventional one; the balanced feed industry is one of the best investment alternatives that allow taking advantage of the by-products of rice mills, corn mills, sugar mill by-products such as molasses, barley bran and yeast in breweries, meat, leather, tallow, pre-mixed viscera, blood meal, feathers and bones of animal by-products. All those by-productsor residues of the industrial process impact the environment in a negative way. The availability of these by-products for animal feed helps to improve the environmental impact and to give a value toa waste whose properties were unknown, and that today is sold at reasonable prices to be used productively in animal feed.